Gender Differences in 3-Month Outcomes of Erenumab Treatment—Study on Efficacy and Safety of Treatment With Erenumab in Men - Ornello, Raffaele; Baraldi, Carlo; Guerzoni, Simona; Lambru, Giorgio; Fuccaro, Matteo; Raffaelli, Bianca; Gendolla, Astrid; Barbanti, Piero; Aurilia, Cinzia; Cevoli, Sabina; Favoni, Valentina; Vernieri, Fabrizio; et al. (Frontiers in Neurology, 2021)
Objective: We reported gender-specific data on the efficacy and safety of erenumab, a monoclonal antibody antagonizing the calcitonin gene-related peptide (CGRP) receptor. Method: Our pooled patient-level analysis of real-world data included patients treated with erenumab and followed-up for 12 weeks. We considered the following outcomes at weeks 9-12 of treatment compared with baseline: 0-29%, 30-49%, 50-75%, and ≥75% responder rates, according to the decrease in monthly headache days (MHDs); rate of treatment stopping; change in MHDs, monthly migraine days (MMDs), monthly days of acute medication and of triptan use, and Headache Impact Test-6 (HIT-6) score from baseline to weeks 9-12. Outcomes were compared between men and women by the chi-squared test or t-test as appropriate. An analysis of covariance (ANCOVA) was performed to identify factors influencing the efficacy outcomes. Results: We included 1410 patients from 16 centers; 256 (18.2%) were men. Men were older than women and had a lower number of MHDs at baseline. At weeks 9-12, compared with baseline, 46 (18.0%) men had a ≥75% response, 75 (29.3%) a 50-74% response, 35 (13.7%) a 30-49% response, and 86 (33.6%) a 0-29% response, while 14 (5.5%) stopped the treatment. The corresponding numbers for women were 220 (19.1%), 314 (27.2%), 139 (12.0%), 401 (34.7%), and 79 (6.8%). No gender difference was found in any of the outcomes. The ANCOVA showed that gender did not influence the efficacy outcomes. Conclusion: We found that erenumab is equally safe and effective in men compared with women after a 12-week period.